Pengembangan Bahan Ajar PAI Materi Qs. Al-Fil Kelas IV SDN 17 Muara Sugihan Berbasis Multimedia - Daryanto Daryanto; Mulyadi Eko Purnomo; Helen Sabera Adib (Bahasa Indonesia, Bahasa English, 2020)
Education that is characterized by the use of technology in learning is education that is in line with the times and globalization. Therefore teachers are required to be able to develop learning that can motivate student interest in learning. Many ways can be done in this case such as developing teaching materials in the form of multimedia learning. Therefore this research develops the PAI teaching material QS al-Fil material for multimedia-based class IV. The method used in this research development is the Research and Development (R and D) method which refers to the Borg and Gall development procedure, with steps as follows: 1) Potential Problems, 2) Data collection, 3) Initial product design, 4) Validation design through FGDs and experts, 5) Design revisions, 6) Product trials. Primary data in this study include interviews, validation sheets (FGD and expert validation),tests to students, and questionnaires to teachers. The secondary data obtained from documentation, books, theses and journals related to research. The results of this study are 1) produce a product namely PAI teaching material QS al-Fil material for classIV SDN 17 Muara Sugihan based on multimedia, 2) expert validation includes material expert validation and application expert validation with an average score of 95% in the very category worthy. 3) the product trial results to see the effectiveness of the product showed a significant difference between before and after the use of the product, namely student learning outcomes increased after the use of the product, while in practicality tests, the practicality of teaching materials tried out for six users obtained an average score 94% with a very decent category.